Quantitative Investigation of Groundwater Contamination at the Afaka Open Dumpsite, Kaduna State, Nigeria: An Integrated Geophysical, Hydrochemical, and Numerical Modeling Approach - Dare, Akinrinshola; Onwuegbunam, Donatus Obiajulu; Maikano, Samson; Bolaji, Olusegun William; Okechalu, Samson Owunebe (FUDMA Journal of Sciences, 2026)
Open dumpsites without protective liners are a massive groundwater pollution problem across the developing world. This study quantifies exactly how the Afaka dumpsite in Kaduna State, Nigeria, is destroying the local water supply. The research team used Vertical Electrical Sounding at ten stations and 2D Electrical Resistivity Tomography along four 200-meter profiles to map groundwater contamination. They also ran numerical models with MODFLOW for groundwater flow and MT3DMS for solute transport. The geophysical data revealed a clear low-resistivity zone (under 25 Ωm) running from 1.2 meters down to 18 meters below the surface. That means toxic leachate has punched straight through the lateritic topsoil and fully saturated the weathered basement aquifer underneath. Water tests from three boreholes backed this up. Wells closest to the dumpsite showed Total Dissolved Solids hitting 1,840 mg/L and Electrical Conductivity at 2,450 μS/cm—more than triple the WHO limits. Heavy metal contamination was severe: Lead at 0.120 mg/L (12× the WHO limit) and Cadmium at 0.015 mg/L (5× the limit).The transient numerical simulations calibrated well, with an RMSE of 0.42 m and R² of 0.98. The models show the contaminant mass spreading steadily down-gradient. Over a 20-year projection, the >250 mg/L isochlor plume will migrate 1.25 kilometers from the dumpsite putting domestic wells directly in harm’s way. To protect public health, this was recommended: capping the dumpsite with an impermeable barrier immediately; installing a pump-and-treat well network to intercept the plume; and banning groundwater pumping within a 500-meter radius.